The effect of acupressure on pain level and hemodynamic parameters after coronary angiography: a randomized controlled study - Barış Düzel; Tuğba Çam Yanik; Canan Kanat; Gülay Altun Uğraş (Frontiers in Cardiovascular Medicine, 2023)
BackgroundSubsequent to coronary angiography, procedures performed to prevent bleeding may cause pain in the patient. In this study, we aimed to determine the effect of acupressure on pain level and hemodynamic parameters in patients undergoing coronary angiography.MethodIn this prospective, a two-arm (1:1), randomized controlled trial was conducted, with 124 patients undergoing coronary angiography included. The randomly assigned study group (n = 62) received acupressure on the LI4 (on the dorsum of the hand, between the 1st and 2nd metacarpal bones), PC6 (three fingers above the wrist), and LI11 (at the lateral end of the transverse cubital crease) points for 15 min 2 h after angiography, while the control group (n = 62) received no acupressure. Data were collected using the visual pain scale (VAS) and hemodynamic parameters [systolic blood pressure (SBP), diastolic blood pressure (DBP), heart rate (HR), respiratory rate (RR), and peripheral oxygen saturation (SpO2)], monitoring form before, immediately after, and at 10, 20, and 30 min after acupressure.ResultsIn the study, it was found that patients had moderate pain after coronary angiography (study group: 5.02 ± 2.27; control group: 3.98 ± 1.82). When the groups were compared, it was found that the VAS score of the study group before angiography was significantly higher than that of the control group, but lower than the control group immediately after acupressure, and at 10, 20, and 30 min after acupressure. In addition, it was determined that acupressure was significantly higher in DBP and RR in the study group compared to the control group at 20 and 30 min; it was not effective in terms of SBP, HR, and SpO2 values.ConclusionThe results of the study indicated that patients reported moderate pain after coronary angiography, and that acupressure was effective in reducing the pain level, but affected only the DBP and RR hemodynamic parameters. Since the study was single-centered and followed for a short time, it is recommended to conduct new studies with a longer duration.